Restructuring Marriage and Family in Industrial Kazakhstan: Axes of Inequality and Conjugality in a Former Soviet Steel Plant - Trevisani, Tommaso (Oriente moderno, 2020)
Abstract This paper addresses how changing patterns of conjugality, family and labour play out in a gender-mixed, multi-ethnic industrial setting built in Soviet times and nowadays owned by foreign corporate capital. Matrimonial relationships among Kazakhstani steel workers have come under sustained pressure as a consequence of privatization and labour restructuring. As a result, workers must accommodate their family lives and partnership prospects to their own precarious situation in an increasingly adverse world of industrial labour. Kazakh, Russian, male, female, precarious and regular workers are differently affected and adopt different strategies. Mirroring workplace related inequalities, marriage and family patterns rooted in distinctive traditions in multi-ethnic Kazakhstan are currently being reshaped. At the same time, marriage and family have become more important in determining workers’ wellbeing at work and beyond.